Development of learning media based on video tutorial on basketball based shooting techniques - Mardiana, Alyu; Doewes, Muchsin; Purnama, Sapta Kunta (Journal of Education, Health and Sport, 2019)
The purpose of this study are: 1) Facilitate and clarify basic basketball technique training material with the video tutorial media. 2) Know how to develop video tutorial based learning media on basketball shooting material that fits the needs and characteristics of students. 3) Know the effectiveness of video tutorial based learning media on basketball shooting material to improve basic basketball techniques. 4) Knowing how much the effectiveness of tutorial video-based learning media on basketball shooting material increases knowledge, understanding students to improve their basic basketball skills. This research was conducted at MAN 1 Ponorogo. The type of research design used is one group pretest-posttest design for one group. This research uses development research methods with a design model of procedural development. This research produced a product in the form of a DVD video tutorial for learning basic shooting techniques in basketball games. The steps for developing video tutorials are: 1) Research and Data Collection, 2) Planning, 3) Product Draft Development, 4) Initial Field Trials, 5) revisions, 6) Small Field Trials, 7) Dissemination and Implementation. The results showed that there was a considerable difference between the pre test and the post test. Namely the pre test value has an average of 72.9, while the post test has an average of 78.1. This means that learning outcomes increase significantly from 72.9 to 78.1. Based on the results above it can be concluded that the product development of video-based learning media based on basketball shooting techniques developed by researchers can improve the ability of basic basketball shooting skills in MAN 1 Ponorogo in class XI students.